A dimension-independent extrusion algorithm using generalised maps - Arroyo Ohori, Ken; Ledoux, Hugo; Stoter, Jantien (International journal of geographical information science : IJGIS, 2015)
One solution to the integration of additional characteristics, for example, time and scale, into GIS data sets is to model them as extra geometric dimensions perpendicular to the spatial ones, creating a higher-dimensional model. While this approach has been previously described and advocated, it is scarcely used in practice because of a lack of high-level construction algorithms and accompanying implementations. We present in this paper a dimension-independent extrusion algorithm permitting us to construct from any (n-1)-dimensional linear cell complex represented as a generalised map, an n-dimensional one by assigning to each (n-1)-cell one or more intervals where it exists along the nth dimension. We have implemented the algorithm in C++11 using CGAL, made the source code publicly available and tested it in experiments using real-world 2D GIS data sets which were extruded to construct up to 5D models.